2014
DOI: 10.7567/jjap.53.04el07
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical impedance spectroscopy in chromatography paper and its application to latex bead detection

Abstract: The principle of the quantitative immunochromatographic strip test (IST) is proposed. Electrochemical impedance spectroscopy is shown to be capable of detecting latex beads in chromatography paper, where latex beads can serve as a label in IST. Measurements to examine the impedance changes in the absence and presence of latex beads are conducted. In the presence of latex beads, an increase of 12.5% in the bulk solution resistance is observed. This indicates that the latex-bead-labeled antigen–antibody complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…35 The feasibility should be verified experimentally because the particle diameter of generally-used AuNPs (of the order of tens of nanometer) 36 is smaller than that of LBs (several micrometer). 34 In addition, it should be also confirmed that the lower limit of the Rsol assay is below that of eye detection. In this paper, we describe the chrono-impedimetry (CI) method used to detect AuNPs by measuring Rsol at a fixed frequency.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…35 The feasibility should be verified experimentally because the particle diameter of generally-used AuNPs (of the order of tens of nanometer) 36 is smaller than that of LBs (several micrometer). 34 In addition, it should be also confirmed that the lower limit of the Rsol assay is below that of eye detection. In this paper, we describe the chrono-impedimetry (CI) method used to detect AuNPs by measuring Rsol at a fixed frequency.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, a study to quantitate IST only with electrodes has been reported. 34 This study focuses on latex beads (LBs) as one widely used label, and measures solution resistance (Rsol) on the detection area in the presence and absence of LBs at a frequency where Rsol dominates the total impedance. This might be the most appropriate quantitation method, since it can be applied to the conventional IST kits without any amendment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, latex microspheres have gained significant attention as a more sensitive label for lateral flow immunoassay strips (LFIA) because the traditional label of colloidal gold cannot meet the detection limit demand. [18][19][20] Hence, in the present study, we developed a rapid immunoassay strip targeting the detection of SARS-CoV-2 antigens. Latex microspheres were used to label the antigens to enhance the detection limit.…”
Section: Introductionmentioning
confidence: 99%